UPAYA PERAN PENYIDIK SAT NARKOBA DALAM PENANGANAN PENYALAHGUNAAN NARKOBA DI WILAYAH HUKUM POLRES KUTAI TIMUR - Chresna Rivan (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT             The drug problem is a national and international problem, because its abuse will negatively impact the lives of the people, nation and state. The development trend of drug crimes in Indonesia recently showed a very sharp increase. One of the results of the National Police's analysis of the high crime rate is one of which is caused by the economic crisis that has hit almost all regions in the republic. With this incident, producers, distributors and consumers take advantage of this situation to enlarge and seek profits in the distribution and abuse of drugs.            In its implementation, the police itself has placed drugs as a case of serious attention and priority, but the tough task certainly will not succeed without the support of all elements of society. The role of the police in tackling drug crime is not only focused on law enforcement alone but also on all efforts shown to reduce the demand and illicit drug needs.            In the area of East Kutai itself, especially the Narcotics case up to July 2018, it has surpassed the Narcotics case in 2017. "Until July, currently the Narcotics Police case handling has reached 63 cases with 71 suspects, even in the last two months of the four suspects secured methamphetamine. weighing more than 130 grams, "Polres and related parties continue to make various efforts to prevent drug abuse in East Kutai, especially Kutim is in the trans Kalimantan route that is open either by land or sea.            Based on this background, the issues in this paper are as follows: (1) What is the Efforts of the Drug Investigation Unit in Dealing with Drug Abuse Cases in the Legal Area of the East Kutai District Police? (2) What are the obstacles faced by Sat Narcotics Investigators in overcoming and misusing Narcotics?            So from the above problems it can be concluded how the efforts of investigators in handling narcotics criminal cases by the Narcotics Police Narcotics Ditserse concluded as follows: (1). Through prevention efforts (preventive efforts) through activities such as by conducting counseling and coaching conducted by the Narcotics Unit cooperating with agencies, giving brochures at the time of counseling and developing Narcotics activities, conducting surveillance in places deemed prone to narcotics abuse, and conducting police operations by patrolling, raiding in places considered vulnerable to narcotics abuse, The Directorate of Drugs conducts both routine and sudden operations. Routine operations are carried out every day through supervision or observation in places that are prone to narcotics abuse. (2) Obstacles faced by drug detective units in the East Kutai Regional Police in overcoming drug abuse, namely: 1. lack of informants in the field, 2. lack of facilities and infrastructure, and 3. limited budget. Keywords: Role of Investigators, Drug Management, Drug Unit